Osseous hamartoma arising from the Eustachian tube - Ai Kawamoto; Yukio Katori; Yohei Honkura; Masaki Ogura; Takeshi Oshima; Toshimitsu Kobayashi (Clinics and Practice, 2013)
A fairly quite rare case of osseous tumor arising from the Eustachian tube (ET) is described. A 56-year-old man presented with a smooth bulky mass in the nasopharynx and secretory otitis media in the right ear. Computed tomography and magnetic resonance imaging indicated a solid tumor-like region occupying the nasopharynx with apparent extension to the right ET. Transnasal endoscopic surgery demonstrated that the tumor had originated from the ET, and the tumor was partially removed in the area where it had expanded into the nasopharynx. The pathological diagnosis was an osseous hamartoma consisting of bony tissue, fat cells and fibroblasts. To our knowledge, this is the first reported case of osseous hamartoma arising from the ET in the world literature. The patient presented symptoms of nasal obstruction and unilateral aural fullness. Reduction surgery and tympanostomy tube insertion were useful for accurate diagnosis and resolution of the symptoms.